Effects of Peptide Thanatin on the Growth and Transcriptome of Penicillium digitatum - Feng, Guirong; Li, Xindan; Wang, Wenjun; Deng, Lili; Zeng, Kaifang (Frontiers in Microbiology, 2020)
Penicillium digitatum is the most damaging pathogen provoking green mold in citrus fruit during storage, and there is an urgent need for novel antifungal agents with high efficiency. The aim of this study was to investigate the antifungal effects of peptide thanatin against P. digitatum and the molecular mechanisms. Results showed that peptide thanatin had a prominent inhibitory effect against P. digitatum by in vitro and in vivo test. A total of 938 genes, including 556 down-regulated and 382 up-regulated genes, were diﬀerentially expressed, as revealed by RNA-seq of whole P. digitatum genome analysis with or without thanatin treatment. The down-regulated genes mainly encoded RNA polymerase, ribosome biogenesis, amino acid metabolism, and major facilitator superfamily (MFS). The genes associated with heat shock proteins (HSPs) and antioxidative systems were more expressed in thanatin treated group. And DNA, RNA and protein contents of P. digitatum were significantly decreased after thanatin treatment. In conclusion, thanatin may inhibit the growth of P. digitatum by disrupting multiple biological processes, especially in genetic information processing and stress response.